Oncologic Outcomes of Robotic Thyroidectomy: 5 Years' Experience. (2nd September 2014) - Tae, Kyung; Ji, Yong Bae; Song, Chang Myeon; Lee, Seung Hwan; Park, Chul Won
Abstract : Objectives: The feasibility and early surgical outcomes of robotic thyroidectomy have been reported. However, its oncologic outcomes are not well established. The aim of this study is to evaluate oncologic outcomes of robotic thyroidectomy compared with conventional thyroidectomy in differentiated thyroid carcinoma (DTC). Methods: We analyzed 925 DTC patients who underwent robotic thyroidectomy (204 cases) using a gasless unilateral axillo‐breast or axillary approach, or conventional open thyroidectomy (721 cases) with or without central neck dissection (CND) from October 2008 to December 2013. We excluded patients who underwent simultaneous lateral neck dissection or completion thyroidectomy and cases with recurrent cancer, other types of malignancy, or distant metastasis. Results: The male ratio and the mean age were significantly lower in the robotic group ( P <. 001). The mean tumor size, minimal extrathyroidal extension, and stage did not differ between the 2 groups. The rate of total thyroidectomy was higher in the open group ( P <. 001). The rate of CND and the mean number of lymph nodes removed in the central compartment was not different between the 2 groups. Operative time was significantly longer in the robotic group ( P <. 001). Postoperative complications did not differ between the 2 groups, except transient hypoparathyroidism. Recurrence rate did not differ between the 2 groups after a mean follow‐up of 33 months (0 % vs 0.4% in the robotic vs open groups, P = 1.0). Conclusions: The oncologic outcome of robotic thyroidectomy in 5 years' experience is comparable with conventional thyroidectomy in selected patients with DTC.